Tunable photonic spin Hall effect due to the chiral Hall effect in strained Weyl semimetals - Guangyi Jia; Ruixia Zhang; Zhenxian Huang; Qiaoyun Ma; Huaiwen Wang; Reza Asgari (New Journal of Physics, 2021)
The latest research suggests that strain can be utilized to engineer the electronic states of Weyl semimetals (WSMs) through creating a pseudo-magnetic field B _el . The response of strained WSMs to a real time-varying electric field E with E ⊥ B _el can cause spatial chirality and charge separation in WSMs, i.e., the chiral Hall effect (CHE). Herein, the photonic spin Hall effect (PSHE) modified by CHE in strained WSM thin films is studied. We show that the in-plane and transverse photonic spin-dependent shifts (⟨Δ x _+ ⟩ and ⟨Δ y _+ ⟩) can be tuned to be more than 400 and 50 times of incident wavelength, respectively, at the angular frequency being close to the cyclotron frequency of massless fermions in the pseudo-magnetic field. In order to enhance the PSHE, epsilon-near-zero materials take priority of being as the substrates of WSM films. Besides, both ⟨Δ x _+ ⟩ and ⟨Δ y _+ ⟩ generally give extreme values around incident angles at which Fresnel reflection coefficients exhibit local minimums, whereas an inversion-symmetry breaking with nonzero axial chemical potential may break this generality. Finally, one possible experimental strategy for observing this CHE tuned PSHE is schemed, which may provide a pristine optical technique to precisely engineer and detect the strain in topological materials.